The Microstructure and Electronic Properties of Yttrium Oxide Doped With Cerium: A Theoretical Insight - Ju, Meng; Wang, Jingjing; Huang, Jing; Zhang, Chuanzhao; Jin, Yuanyuan; Sun, Weiguo; Li, Shichang; Chen, Yunhong (Frontiers in Chemistry, 2020)
Trivalent Cerium (Ce3+) doped Yttrium Oxide (Y2O3) host crystal has drawn considerable interest due to its popular optical 5d-4f transition. The outstanding optical properties of Y2O3:Ce system have been demonstrated by previous studies but the microstructures still remain unclear. The lacks of Y2O3:Ce microstructures could constitute a problem to further exploit its potential applications. In this sense, we have comprehensively investigated the structural evolutions of Y2O3:Ce crystals based on the CALYPSO structure search method in conjunction with density functional theory calculations. Our result uncovers a new rhombohedral phase of Y2O3:Ce with R-3 group symmetry. In the host crystal, the Y3+ ion at central site can be naturally replaced by the doped Ce3+, resulting in a perfect cage-like configuration. We find an interesting phase transition that the crystallographic symmetry of Y2O3 changes from cubic to rhombohedral when the impurity Ce3+ is doped into the host crystal. With the nominal concentration of Ce3+ at 3.125%, many metastable structures are also identified due to the different occupying points in the host crystal. The X-ray diffraction patterns of Y2O3:Ce are simulated and the theoretical result is comparable to experimental data, thus demonstrating the validity of the lowest energy structure. The result of phonon dispersions shows that the ground state structure is dynamically stable. The analysis of electronic properties indicate that the Y2O3:Ce possesses a band gap of 4.20 eV which suggests that the incorporation of impurity Ce3+ ion into Y2O3 host crystal leads to an insulator to semiconductor transition. Meanwhile, the strong covalent bonds of O atoms in the crystal, which may greatly contribute to the stability of ground state structure, are evidenced by electron localization function. These obtained results elucidate the structural and bonding characters of Y2O3:Ce and could also provide useful insights for understanding the experimental phenomena.